2012
DOI: 10.3410/f1000research.1-20.v1
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of disinfectants on abattoirs’ Candida albicans isolates in Niger Delta region

Abstract: This study was conducted to evaluate the antimicrobial activities of common disinfectants-these are (parachlorometaxylenol) dettol, savlon purit and jik (sodium hypochlorite) on isolated from Candida albicans displaying and cutting tables in five different abattoirs in Port Harcourt (Niger Delta region); the abattoirs include Trans Amadi, Agip, Woji, Rumuokoro, and Rumuodara. This research was carried out between January 2005 and June 2006. Swab samples were collected from abattoirs cutting tables with sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Total inhibition of C. albicans was achieved in 180 s with 5,000 ppm PCMX and in 60-90 s with 50,000 ppm PCMX [32]. Other reports indicated that 5,000 ppm totally inhibited C. albicans after 20 min [33]. The MLC (minimal lethal concentration) of PCMZ against Staphylococcus aureus was reported to be 1,250 ppm [34].…”
Section: Percent Inhibition Of C Albicans By Pcmx Cu and The Mixturementioning
confidence: 99%
“…Total inhibition of C. albicans was achieved in 180 s with 5,000 ppm PCMX and in 60-90 s with 50,000 ppm PCMX [32]. Other reports indicated that 5,000 ppm totally inhibited C. albicans after 20 min [33]. The MLC (minimal lethal concentration) of PCMZ against Staphylococcus aureus was reported to be 1,250 ppm [34].…”
Section: Percent Inhibition Of C Albicans By Pcmx Cu and The Mixturementioning
confidence: 99%
“…HIV-positive) individuals [4,5]. C. albicans can grow in a variety of morphological forms, ranging from yeast form to pseudohyphae form to true tubular hyphae form, depending on the growth conditions in the host environment [6].…”
Section: Introductionmentioning
confidence: 99%